2020
DOI: 10.1001/jamainternmed.2020.0555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Paradigm Shift From Intravenous Antibiotics to Oral Step-Down Therapy for the Treatment of Infective Endocarditis

Abstract: dogma in medicine has long been that effective treatment of infective endocarditis (IE) requires prolonged intravenous antibiotic therapy. This dogma developed during an era when penicillin was the most effective antibiotic to treat IE, for which it was only administered intravenously because its oral absorption was regarded as unreliable. The underpinning of this dogma was the rationalization that a high number of bacteria are "buried" deep within cardiac vegetations, limiting both antimicrobial access and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…For the synthesis of target molecules 4, palladium nanoparticles catalysed reaction was selected [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], ( Figure 2 ). Preliminary studies on reaction between phenylboronic acid and vinyl acetate showed that commercially available palladium nanoparticles Pd0 EnCat 30NP in the presence of benzoquinone ( 3 ) proceed in water at room temperature in 1% yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the synthesis of target molecules 4, palladium nanoparticles catalysed reaction was selected [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], ( Figure 2 ). Preliminary studies on reaction between phenylboronic acid and vinyl acetate showed that commercially available palladium nanoparticles Pd0 EnCat 30NP in the presence of benzoquinone ( 3 ) proceed in water at room temperature in 1% yield.…”
Section: Resultsmentioning
confidence: 99%
“…This compound was found to have antioxidant and anti-inflammatory properties [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Recently special attention was paid on combrestatin for its antimicrobial activity [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Due to its biological activity, combre...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, oral therapy entails normal gastrointestinal uptake and good adherence, ensured in non-self-administered OPAT. Antibiotic exposure in high inoculum infections after oral antibiotic administration depends on the pharmacokinetics profile of each drug, and nowadays it is a matter of discussion, especially regarding β-lactam oral therapy [ 13 , 43 , 44 ]. In this trial, seven patients in the oral therapy arm showed antibiotic plasma concentrations lower than the effective level, whereas no regimen adjustment was made on that base [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The factors that cause pathological changes in the structure and/or function of the heart are diverse, such as coronary ischaemic heart diseases [ 25 ], severe congenital heart diseases [ 26 ], and heart dysfunction caused by certain bacterial or viral infections [ 27 ]. The pathophysiology that specifically affects one or more layers of myocardial tissue is moreover highly heterogeneous; and if the lesions are treated inappropriately or they are too complicated to cure, this often leads to intractable heart failure [ 28 ].…”
Section: Anatomy Of Heart and Cardiac Diseasesmentioning
confidence: 99%